Informe de consultoría sobre pudriciones radiculares en leguminosas de grano - Abawi, Gorge S. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The document marks as the main objective to identify and determine the importance of root disease problems on food legume crops in the Andean subregion of south America (Bolivia, Peru, Ecuador, Colombia, and Venezuela). A secondary objective is to provide an informal training in the diagnosis, symptomatology, appropriate management strategies, and prioritizing research needs on these crops (Beans, Peas, Broadbeans, Lentils, Ckickpeas and others). The document is a brief summary of the observations and rot diseases diagnosed in each of the five countries visited. The information provided should not be considered as complete or final because the time of the evaluation is not the most appropriate for each production area or for all leguminous crops grown in these areas, among other things. At the end, it explains that the main contribution of this job is the identification of the major root rot diseases of legume crops in the different production areas in the Andean subregion countries. This information will increase contacts among institutions and researchers in these countries and thus the increased exchange of research results and the possible coordinations of future research efforts. In addition, production technologies that developed for one area or are now known to reduce diseases and increase yield will undoubtly be of interest and thus may be transfered to other regions of similar needs. The potential increase in cooperation and transfer of technologies among the countries will increase the efficiency of research efforts and at the same time shorten the time needs for their delivery and adaptations.